Subacromial resurfacing with fascia lata autograft for irreparable cuff tears - Nuno Gomes; Helder Fonte; Sara Santos; Duarte Sousa (Journal of Experimental Orthopaedics, 2021)
Abstract Massive and irreparable rotator cuff tears remain a major challenge for orthopaedic surgeons and several surgical options have been accepted for different patterns of irreparable cuff tears. However, the high‐cost and technical complexity of some surgeries and the inconsistent clinical results of others, leave room for the search for surgical options that can offer a good balance between technical simplicity, a lower cost and an acceptable clinical result. The rationale behind some available techniques includes lowering the humeral head, which enables a more efficient balance of the force couples around the shoulder during rehabilitation. The interpositional arthroplasty with a biodegradable balloon, the Superior Capsule Reconstruction and, more recently, subacromial resurfacing with a dermal allograft have been presented as valid options to address that purpose. This technical note presents Subacromial Resurfacing with fascia lata as an option for the treatment of irreparable rotator cuff tears in the elderly population. Its low‐cost and reasonable technical demand, along with the need for further elucidation of the ideal indications and technical optimization of other available techniques may open up room for the success of this option.